Comprehensive analysis of eccDNA characteristics and associated genes expression in peripheral blood of ASLE and ISLE patients - Yali Peng; Huihui Tao; Dongzhou Liu; Donger Tang; Chunmei Wen; Mengyao Wu; Tiantian Xu; Guoying Wang; Xuejia Zheng; Yong Dai (Epigenetics)
To explore SLE staging markers, we analyzed eccDNA in plasma using circular sequencing, comparing healthy controls (HC), active SLE (ASLE), and inactive SLE (ISLE) patients. We found higher eccDNA levels and lower GC content in ASLE and ISLE compared to healthy controls, with a negative correlation between GC content and anti-daDNA, C3, and C4 levels in SLE and HC samples. Differential expression of exon-derived eccGenes in ASLE and ISLE suggests their role in SLE development, with KEGG analysis showing enrichment in SLE-related pathways for these differentially expressed genes. By protein–protein interactions network analysis we found 9 exon-derived eccGenes that were significantly differentially expressed and scored high in both ISLE-HC and ASLE-ISLE as diagnostic criteria for differentiating different disease stages of SLE. In conclusion, the present study reveals that eccDNA length GC content as well as chromosomal distribution in ASLE, ISLE and HC suggests that with eccDNA is associated with the creation of SLE, suggesting GC count of eccDNA as a diagnostic marker for systemic lupus erythematosus. Significant changes in the abundance of eccDNA-related genes from exons such as SOS1, GAD2, BCL11B, PPT1, and GCNT3 were observed in ISLE as compared to ASLE and HC groups and were significantly correlated with SLEDAI-2K. This suggests that these exon-derived eccGenes may play a role in the development and progression of the disease. Consequently, the abundance levels of these exon-derived eccGenes could potentially assist in distinguishing different stages of SLE, beyond a confirmed diagnosis, thus serving as possible biomarkers for the condition.